2015
DOI: 10.1007/s00586-015-4252-z
|View full text |Cite
|
Sign up to set email alerts
|

Delayed postoperative C5 root palsy and the use of neurophysiologic monitoring

Abstract: Patients undergoing cervical decompression remain at risk for C5 root palsy despite use of monitoring. Given that all patients experienced delayed onset of C5 palsy, MEP, SSEP, and EMG may not be sensitive enough to assess the risk of developing C5 palsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
2
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 17 publications
0
7
2
3
Order By: Relevance
“…Yet, differentiation between these two possibilities could not be made. It has been also known that monitoring MEPs from deltoid muscle could fail to detect radicular lesion of C5 root and consecutively paresis of deltoid muscle (Spitz et al, 2015, Yanase et al, 2010). Furthermore, disappearance of MEPs in deltoid muscle is not always correlated with clinical outcome (Clark et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, differentiation between these two possibilities could not be made. It has been also known that monitoring MEPs from deltoid muscle could fail to detect radicular lesion of C5 root and consecutively paresis of deltoid muscle (Spitz et al, 2015, Yanase et al, 2010). Furthermore, disappearance of MEPs in deltoid muscle is not always correlated with clinical outcome (Clark et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Peroperative neurophysiologic monitoring seemed of little value, electromyogram and somatosensory evoked potentials not being sensitive enough and having no predictive value. 14 Rowland et al 15 confirmed…”
Section: Does C5 Nerve Root Palsy Occur?mentioning
confidence: 94%
“…A fisiopatologia da paralisia pós-operatória (PO) de C5 ainda não é bem compreendida. A migração posterior da medula espinhal cervical após descompressão é uma das principais hipóteses [1][2][3][4][5][6][7][8][9][10][11] . Esta hipótese foi sustentada pelos achados obtidos por Sounders et al, que obteve redução significativa de radiculopatia C5 -de 14,6 % para 2,5% -diminuindo a extensão da corpectomia central de 20 para 15 milímetros 2 .…”
unclassified
“…Pode haver dor residual em cerca de 20% dos casos 11 . A recuperação é espontânea, o que justifica o emprego de tratamento conservador [1][2][3][4][5][6][7][8][9][10][11] .…”
unclassified
See 1 more Smart Citation